Resident Immunity in Tissue Repair and Maintenance: The Zebrafish Model Coming of Age - Martins, Raquel Rua; Ellis, Pam S.; MacDonald, Ryan B.; Richardson, Rebecca J.; Henriques, Catarina Martins (Frontiers in Cell and Developmental Biology, 2019)
The zebrafish has emerged as an exciting vertebrate model to study different aspects of immune system development, particularly due to its transparent embryonic development, the availability of multiple fluorescent reporter lines, efficient genetic tools and live imaging capabilities. However, the study of immunity in zebrafish has largely been limited to early larval stages due to an incomplete knowledge of the full repertoire of immune cells and their specific markers, in particularly, a lack of cell surface antibodies to detect and isolate such cells in living tissues. Here we focus on tissue resident or associated immunity beyond development, in the adult zebrafish. It is our view that, with our increasing knowledge and the development of improved tools and protocols, the adult zebrafish will be increasingly appreciated for offering valuable insights into the role of immunity in tissue repair and maintenance, in both health and disease throughout the lifecourse.